European genizah newly discovered Hebrew binding fragments in context - Lehnardt, Andreas 1965- (Boston Brill, 2020)
"This volume includes contributions presented at two conferences, in Mainz and Jerusalem, and presents new discoveries of binding fragments in several European libraries and archives and abroad. It presents newly discovered texts with unknown Jewish writings from the Middle Ages and analyses fragments of well-known texts, such as textual witnesses of Midrashim. One chapter overviews recent discoveries in certain collections, some of them far beyond the geographical horizon of the original project, but certainly all of European origin. Other chapters study palaeographical and codicological issues of manuscript fragments and Ashkenazic inscriptions. A final article refers to the beginnings of scholarly interest in Hebrew binding fragments in Germany and sheds light on the part played by Christian Hebraists in its development"--
Includes bibliographical references and index
Keywords: Manuscripts, Medieval -- Europe -- Congresses; Paleography, Hebrew -- Congresses; Judaism -- History -- Medieval and early modern period, 425-1789; Rabbinical literature -- Bibliography; Manuscripts, Hebrew -- Europe -- Congresses; Europe -- History; Aufsatzsammlung